Normative Analysis of Sheikh Bin Baz's Fatwa On Marriage With The Intention Of Divorce - Ahmad Raihan; Gusti Muzainah (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract Avoiding adultery is often a reason for people to hasten marriage. However, an interesting phenomenon that needs to be studied is "marriage with the intention of divorce," where a man marries a woman with the intention of divorcing her after fulfilling his needs or completing his studies, as a way to avoid adultery. An important concept to analyze in this context is "maslahah mursalah". However, is this kind of marriage justifiable within the framework of the public good and is the fatwa allowing it based on the principles of "maslahah mursalah"? This study used a qualitative approach and found that Sheikh Bin Baz's fatwa permits marriage with the intention of divorce and is not considered a betrayal of the future wife. However, it is important to note that this intention should not be mentioned during the marriage contract and should not be expressed directly to the future wife. In addition, this kind of marriage contradicts the principles of applying "maslahah mursalah" and does not meet the objectives of marriage mentioned in the marriage law and Islamic law (KHI), namely happiness and permanence, and the realization of a sakinah, mawaddah and rahmah household life. Keywords: Marriage, intention, divorce, fatwa, Syeikh Bin Baz, legal objectives, maslahah mursalah Abstrak Menghindari perzinahan sering kali menjadi alasan bagi seseorang untuk mempercepat pernikahan. Namun, fenomena menarik yang perlu diteliti adalah "pernikahan dengan niat cerai," di mana seorang pria menikahi seorang wanita dengan niat untuk menceraikannya setelah memenuhi kebutuhannya atau menyelesaikan studi, sebagai cara untuk menghindari perzinahan. Konsep yang penting untuk dianalisis dalam konteks ini adalah "maslahah mursalah". Namun, apakah pernikahan semacam ini dapat dibenarkan dalam kerangka kemaslahatan umum dan apakah fatwa yang mengizinkannya didasarkan pada prinsip-prinsip "maslahah mursalah"? Penelitian ini menggunakan pendekatan kualitatif dan menemukan bahwa fatwa Syekh Bin Baz memperbolehkan pernikahan dengan niat cerai dan tidak dianggap sebagai pengkhianatan terhadap calon istri. Namun, penting untuk dicatat bahwa niat ini tidak boleh disebutkan saat akad nikah dan tidak boleh diungkapkan secara langsung kepada calon istri. Selain itu, pernikahan semacam ini bertentangan dengan prinsip-prinsip penerapan "maslahah mursalah" dan tidak memenuhi tujuan perkawinan yang disebutkan dalam undang-undang perkawinan dan hukum Islam (KHI), yaitu kebahagiaan dan keabadian, serta terwujudnya kehidupan rumah tangga yang sakinah, mawaddah, dan rahmah. Kata Kunci : Nikah, Niat, Talak, Fatwa, Syeikh bin Baz, Tujuan Hukum, Maslahah Mursalah.